Self-Adhesive Luting Composites: Effect of Curing-Mode and Storage on KIc. (2022) - Woeschler, A.; Belli, R.; Lohbauer, U.; Petschelt, A.; Zorzin, J.
Abstract : Purpose/Aim: The aim of the present study was to investigate the influence of curing-mode (dual or self-curing) and storage time (24 h, 14 d, 60 d) on the fracture toughness (KIc) of self-adhesive luting composites (SALCs). Materials and Methods: The KIc of four different SALCs (RXU2, RelyX Unicem 2, 3 M ESPE; GCLA, G-Cem LinkAce; GC-Corporation; iCEM, iCem Self Adhesive, Kulzer; PAN, Panavia SA Universal Cement, Kuraray Noritake) was measured using the Chevron-Notched Beam method. From each material, 30 samples were prepared in dual-curing mode (20 s @ 1200 mW/cm2, 8 mm light-tip) and 30 samples in self-curing mode (curing-time according to manufacturer). All specimens were stored in artificial saliva in the dark at 37 C. KIc was measured after 24 h, 14 and 60 d (n=10 per material, curing-mode and storage time). Statistical analysis was performed with a t-test of independent samples and a single factor ANOVA (alpha=0.05). Results: The curing mode had a significant influence on KIc, within the same material and storage time (p<.05), with exception of RXU2, GCLA and iCEM after 60 d. In general, the KIc of dual-cured specimens was significantly higher, except for RUX2 in self-cure mode after 24 h (p>.05). After 60 d of storage all materials, independently of the curing-mode, had a significant decrease in KIc (p<.05). Only PAN had any decrease in KIc. Under the same curing-mode and storage time, GCLA showed the significantly highest KIc (p<.05), whereas iCEM the lowest, with exception of the its 24 h dual-cure group. Conclusions: Within the limits of this study, it can be concluded that the mechanical stability of the SALCs under investigation, in terms of KIc, is influenced by curing-mode and storage time. The extent of mechanical deterioration is material dependent. The in-vitro measured decays in KIc could lead in-vivo to deterioration of the adhesive interface and in consequence to restoration loss or fracture. The long-term resilience to water degradation and chemical curing of SALCs show potential of improvement.